2017
DOI: 10.1111/jerd.12348
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage around zirconia crown margins after ultrasonic scaling with self‐adhesive resin or resin modified glass ionomer cement

Abstract: Piezoelectric ultrasonic scaling around zirconia crowns did not impact marginal microleakage cemented with self-adhesive resin or RMGI cements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
2
7
1
1
Order By: Relevance
“…This was observed also on examining the sectioned crowns, where the dye stain was more intense at the resin cement/tooth interface, which proved that group II specimens expressed higher microleakage percentage than those of group I. This was in accordance with the findings of Chang et al (28) Furthermore, when comparing the results of each group alone, there was a higher microleakage percentage after application of ultrasonic scaling especially when using the self-adhesive resin cement, though this was not significantly observed in case of self-etch adhesive resin cement group. This proves that piezoelectric ultrasonic scaling may affect and disrupt the bond formed at any restoration/tooth interface.…”
Section: F: F For Anova Test Pairwise Comparison Between Each 2 Grousupporting
confidence: 88%
See 4 more Smart Citations
“…This was observed also on examining the sectioned crowns, where the dye stain was more intense at the resin cement/tooth interface, which proved that group II specimens expressed higher microleakage percentage than those of group I. This was in accordance with the findings of Chang et al (28) Furthermore, when comparing the results of each group alone, there was a higher microleakage percentage after application of ultrasonic scaling especially when using the self-adhesive resin cement, though this was not significantly observed in case of self-etch adhesive resin cement group. This proves that piezoelectric ultrasonic scaling may affect and disrupt the bond formed at any restoration/tooth interface.…”
Section: F: F For Anova Test Pairwise Comparison Between Each 2 Grousupporting
confidence: 88%
“…This was in agreement with the findings of several authors. (19,25,28) However, the values of microleakage for the self-adhesive resin cement reported in this current study, showed lower values as compared to other previous studies. (6,28) This might be due to the use of cements supplied from different companies and therefore may contribute to varying bonding to dentin.…”
Section: F: F For Anova Test Pairwise Comparison Between Each 2 Groucontrasting
confidence: 71%
See 3 more Smart Citations